Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1213/01.ane.0000284666.39224.05
|View full text |Cite
|
Sign up to set email alerts
|

Leadership of United States Academic Anesthesiology Programs 2006: Chairperson Characteristics and Accomplishments

Abstract: The survey suggests that anesthesiology chairs value peer-reviewed research, scholarship, and academic achievement, but do not believe that significant research experience is of great benefit to functioning as a chair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Program director status was determined from Accreditation Council of Graduate Medical Education databases. These data were compared with survey data using Fisher's exact test [3], and they were also previously reported [2], showing that respondent data and independent data were not different (Table 1).…”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…Program director status was determined from Accreditation Council of Graduate Medical Education databases. These data were compared with survey data using Fisher's exact test [3], and they were also previously reported [2], showing that respondent data and independent data were not different (Table 1).…”
Section: Methodsmentioning
confidence: 64%
“…Culley et al [9] demonstrated that anesthesia chairs, when compared with surgical chairs, have less NIH grant funding (30% vs. 60%) and PubMed citation rates (50 ± 51 vs. 133 ± 98), respectively, over the duration of their careers. Another reason the respondents considered "fostering research and scholarship" as the most difficult management challenge, may be that they ranked as least important in preparation to be a chair "establishing a research center with the goal of NIH funding" [2]. This suggests that they may not have developed the skills to foster research and scholarship within their departments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sur cet emploi, le candidat tire aujourd'hui profit pour densifier la liste de ses travaux mais cette position devrait constituer é galement une opportunité pour inté grer un projet professionnel structuré de formation et de mise en responsabilité managé riale. Il est inté ressant de souligner qu'aux É tats-Unis, les chefs de service d'anesthé sie des structures universitaires considè rent que l'é tape la plus formatrice dans leur parcours est d'avoir occupé , pré alablement à leurs fonctions actuelles, un poste de responsabilité s couvrant les champs cliniques, administratifs, pé dagogiques et de recherche au sein d'une structure d'anesthé sie [6].…”
Section: Dé Velopper Le Mentoratunclassified